Phytochemical Screening and Evaluation of Diuretic Activity of Methanolic Extract of Leaves of Neolamarckia Cadamba - Singh, Shikha; Jain, Vinay (Journal of Neonatal Surgery, 2025)
The phytochemical components and diuretic efficacy of the methanolic extract of Neolamarckia cadamba leaves are investigated in this work. Rich phytoconstituent profile was indicated by preliminary phytochemical screening, revealing alkaloids, flavonoids, tannins, saponins, glycosides, and phenolic compounds. Using adult Wistar albino rats, the diuretic action was evaluated under a standard medication furosemide. Urinary volume and electrolyte excretion (Na⁺, K⁺, and Cl⁻) showed a notable rise in the extract at two dosage levels—200 mg/kg and 400 mg/kg—versed against the control group. The promising diuretic action of the methanolic extract of Neolamarckia cadamba leaves supports its traditional usage in the treatment of fluid retention problems. More investigation is advised to separate and define the bioactive substances causing the reported pharmacological effects